ANALISIS PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN UNTUKMENDORONG MINAT BELI ULANG (Studi Pada Pengguna Kartu Indosat Ooredoo) - Ana Mentaldi (MNJ 16 UMY 147, 2016)
This research aims to give solution upon the decreasing problem of sale level, share market, and disatisfaction of Ooredoo Indosat Card users in Yogyakarta by examining the influence analysis of product and service quality on customer satisfaction to increase repurchase intention. The research was conducted in Yogyakarta with total number of samples as many as 96 people. The samples were taken using purposive sampling and based on given criteria. The data collecting technique used for this research by distributing quetionnaires to Ooredoo Indosat card users in Yogyakarta. The result of the testing using multiple linear regression and simple regression showed that the product and service quality indeed has positive significant influence toward the customer satisfaction. Furthermore, the customer satisfaction has positive significant influence toward repurchase intention. Key Words: product quality, service quality, customers’ satisfaction, repurchase intention